# How to solve:- a=x(2x+3)-4(x+1-)2x(x-1/2) ?

Welcome to my article a=x(2x+3)-4(x+1)-2x(x-1/2) ?This question is taken from the simplification lesson.
The solution of this question has been explained in a very simple way by a well-known teacher by doing addition, subtraction, and fractions.
For complete information on how to solve this question a=x(2x+3)-4(x+1)-2x(x-1/2)? read and understand it carefully till the end.

Let us know how to solve this question a=x(2x+3)-4(x+1)-2x(x-1/2)?

First write the question on the page of the notebook.

## a=x(2x+3)-4(x+1)-2x(x-1/2)

writing this question correctly in this way,

\displaystyle a=x\left( {2x+3} \right)-4\left( {x+1} \right)-2x\left( {x+\frac{{-1}}{2}} \right) ,

Let us now solve this line by line.

\displaystyle a=x\left( {2x+3} \right)-4\left( {x+1} \right)-2x\left( {x-\frac{1}{2}} \right) ,

\displaystyle a=x\left( {2x+3} \right)-4\left( {x+1} \right)-2x\times x-2x\times -\frac{1}{2} ,

\displaystyle a=x\left( {2x+3} \right)-4\left( {x+1} \right)-2{{x}^{2}}+\frac{{2x}}{2} ,

\displaystyle a=x\left( {2x+3} \right)-4\left( {x+1} \right)-2{{x}^{2}}+\frac{2}{2}x ,

\displaystyle a=x\left( {2x+3} \right)-4\left( {x+1} \right)-2{{x}^{2}}+x ,

\displaystyle a=x\left( {2x+3} \right)-4\times x-4\times 1-2{{x}^{2}}+x ,

\displaystyle a=x\left( {2x+3} \right)-4x-4-2{{x}^{2}}+x ,

\displaystyle a=x\left( {2x+3} \right)-4x+x-2{{x}^{2}}-4 ,

\displaystyle a=x\left( {2x+3} \right)-3x-2{{x}^{2}}-4 ,

\displaystyle a=x\times 2x+x\times 3-3x-2{{x}^{2}}-4 ,

\displaystyle a=2{{x}^{2}}+3x-3x-2{{x}^{2}}-4 ,

\displaystyle a=2{{x}^{2}}-2{{x}^{2}}+3x-3x-4 ,

\displaystyle a=3x-3x-4 ,

\displaystyle a=-4 ,

In this way, after doing this question line by line, its intended solution is –